Congress volume Ljubljana 2007 - Lemaire, André, 1942- (Vetus Testamentum, Supplements, 2010)
This volume presents all the main lectures of the XIXth Congress of the International Organization for the Study of the Old Testament (IOSOT) held in Ljubljana (July 2007). It is a very good sample of the main trends and progress of current biblical research on masoretic tradition, Hebrew philology, textual criticism, literary criticism (especially in prophetic books), ancient Judaism, formation of the collections of Ancient Scriptures, and biblical themes (especially according to the orthodox tradition of interpretation). The thirty-one authors are among the main international figures of current biblical exegesis and their contributions are representative of the study of the Old Testament at the beginning of the third millennium.